Interactive map based solar computation program [electronic resource] - 381105 Wong, Fong Yee (Skudai : Universiti Teknologi Malaysia, 2008)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik) - Universiti Teknologi Malaysia, 2008